Hybridity and National Identity in Post-colonial Schools - Azada-Palacios, Rowena A (Archīum Ateneo, 2021)
The recent resurgence of extreme-right movements and the nationalist turn of many governments across the world have reignited the relevance of discussions within educational philosophy about the teaching of national identity in schools. However, the conceptualisation of national identity in previous iterations of these debates have been largely Western and Eurocentric, making the past theoretical literature about these questions less relevant for post-colonial settings. In this paper, I imagine a new approach for teaching national identity in post-colonial contexts, founded on postcolonial conceptions of identity and in particular, the concept of hybridity. I first develop a postcolonial account of national identity by drawing on Homi Bhabha’s thinking about cultural identity, drawing on his concepts of liminality, splitting, and ambivalence. Then, building on Bhabha's notion of hybridity, I propose a distinction between national identity portrayals as either fixed or malleable. Finally, I demonstrate the implications of such a conceptual distinction on the way that national identity is taught in post-colonial schools; by way of an example, I envision a concrete approach to teaching national identity that views national identity as malleable rather than fixed, set in a hypothetical postcolonial school in the Philippines. By beginning from postcolonial assumptions about national identity, I hope to indicate new directions that the debates about the teaching of national identity in schools might proceed.